Growth rates of pulmonary metastases after liver transplantation for unresectable colorectal liver metastases. Issue 3 (23rd November 2017) - Grut, H.; Solberg, S.; Seierstad, T.; Revheim, M. E.; Egge, T. S.; Larsen, S. G.; Line, P. D.; Dueland, S.
Abstract : Background: The previously reported SECA study demonstrated a dramatic 5‐year survival improvement in patients with unresectable colorectal liver metastases (CLM) treated with liver transplantation (LT) compared with chemotherapy. The objective of this study was to assess whether immunosuppressive therapy accelerates the growth of pulmonary metastases in patients transplanted for unresectable CLM. Methods: Chest CT scans from 11 patients in the SECA study resected for 18 pulmonary metastases were reviewed retrospectively. Tumour diameter, volume and CT characteristics were registered and tumour volume doubling time was calculated. Findings in the SECA group were compared with those of a control group consisting of 12 patients with non‐transplanted rectal cancer resected for 26 pulmonary metastases. Disease‐free survival (DFS) and overall survival (OS) after first pulmonary resection were determined. Results: Median doubling time based on tumour diameter and volume in the SECA and control groups were 125 and 130 days ( P = 0·658) and 110 and 129 days ( P = 0·632) respectively. The metastases in both groups were distributed to all lung lobes and were mostly peripheral. Median DFS after LT in the SECA group and after primary pelvic surgery in the control group was 17 (range 6–42) and 18 (2–57) months respectively ( P = 0·532). In the SECA group, estimated 5‐year DFS and OS rates after first pulmonary resection were 39 and 51 per cent respectively. Conclusion: Patients treated by LT for unresectable CLM have a good prognosis following resection of pulmonary metastases. Doubling time did not appear to be worse with the immunosuppression used after LT. Abstract : Immunosuppression may not accelerate growth